(untitled) (Bangladesh Journal of Scientific and Industrial Research, 2025)
The quality of pounded yam made from three different Dioscorea rotundata cultivars was assessed using three different processing methods: mortar and pestle, pounding machine, and attrition mill. The functional and pasting properties of yam starch, as well as the textural characteristics of pounded yam, were evaluated. The functional qualities of yam starch yielded values ranging from 10.36 to 12.81 g/g, 3.50 to 4.76%, 25.52 to 40.83%, and 81.00 to 83.00% for swelling power, solubility index, water absorption capacity, and dispersibility, respectively. The peak, breakdown, final, and setback viscosities of yam starch ranged from 571.09 to 682.67 (RVU), 302.96 to 355.29, 378.29 to 591.13, and 119.75 to 324.96 RVU, respectively. The scientific and subjective approaches for evaluating the samples revealed similar characteristics. The judges’ acceptance of the pounded yam samples was significantly influenced by both the processing procedures and the yam cultivars. Bangladesh J. Sci. Ind. Res. 60(2), 83-92, 2025